Formation Of Active Citizenship Competences In Children With Hearing Problems - Fozilov Botirjon Zakirovich (Euro Asian Journal Publishing, 2023)
This article describes the current issues of active citizenship formation in children with hearing problems, the tasks set in the process of forming legal education in educational activities.
Keywords: Children with disabilities; deaf and hard-of-hearing children; educator